Stock Market Behavior on Ex-Dividend Dates: The Case of Cum-Ex Transactions in Germany - Carolin Holzmann; Hendrik Scholz; Felix Kreidl; Thiess Büttner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
The paper explores the effect of cum-ex trading on the stock market on ex-dividend days. A loophole in the German withholding tax system until 2011 enabled cum-ex traders to achieve the issuance of cash-equivalent withholding-tax certificates without previous tax payment. The paper discusses the implications for the capital market equilibrium and derives empirical predictions for stock market behavior. The results indicate a major impact of the loophole on the capital market and trading volumes.
Keywords: H25; H26; G12; 330